Assessing the role of extracellular signal‐regulated kinases 1 and 2 in volume overload‐induced cardiac remodelling. (19th July 2019) - Jochmann, Svenja; Elkenani, Manar; Mohamed, Belal A.; Buchholz, Eric; Lbik, Dawid; Binder, Lutz; Lorenz, Kristina; Shah, Ajay M.; Hasenfuß, Gerd; Toischer, Karl; Schnelle, Moritz
Abstract: Aims: Volume overload (VO) and pressure overload (PO) induce differential cardiac remodelling responses including distinct signalling pathways. Extracellular signal‐regulated kinases 1 and 2 (ERK1/2), key signalling components in the mitogen‐activated protein kinase (MAPK) pathways, modulate cardiac remodelling during pressure overload (PO). This study aimed to assess their role in VO‐induced cardiac remodelling as this was unknown. Methods and results: Aortocaval fistula (Shunt) surgery was performed in mice to induce cardiac VO. Two weeks of Shunt caused a significant reduction of cardiac ERK1/2 activation in wild type (WT) mice as indicated by decreased phosphorylation of the TEY (Thr‐Glu‐Tyr) motif (−28% as compared with Sham controls, P < 0.05). Phosphorylation of other MAPKs was unaffected. For further assessment, transgenic mice with cardiomyocyte‐specific ERK2 overexpression (ERK2tg) were studied. At baseline, cardiac ERK1/2 phosphorylation in ERK2tg mice remained unchanged compared with WT littermates, and no overt cardiac phenotype was observed; however, cardiac expression of the atrial natriuretic peptide was increased on messenger RNA (3.6‐fold, P < 0.05) and protein level (3.1‐fold, P < 0.05). Following Shunt, left ventricular dilation and hypertrophy were similar in ERK2tg mice and WT littermates. Left ventricular function was maintained, and changes in gene expression indicated reactivation of the foetal gene program in both genotypes. No differences in cardiac fibrosis and kinase activation was found amongst all experimental groups, whereas apoptosis was similarly increased through Shunt in ERK2tg and WT mice. Conclusions: VO‐induced eccentric hypertrophy is associated with reduced cardiac ERK1/2 activation in vivo . Cardiomyocyte‐specific overexpression of ERK2, however, does not alter cardiac remodelling during VO. Future studies need to define the pathophysiological relevance of decreased ERK1/2 signalling during VO.